Construction of a tandem HZSM-5 with CuZnAl catalyst for alkylation of benzene with syngas. (28th January 2020) - Gao, Bize; Ding, Chuanmin; Wang, Junwen; Ding, Guangyue; Dong, Jinxiang; Ge, Hui; Li, Xuekuan
Abstract : A bifunctional catalyst composed of ZSM-5 and Cu–Zn–Al shows an outstanding catalytic performance in the alkylation reaction of benzene with syngas. Abstract : Aiming at the problem of over-production of benzene and the demand for aromatics in industry, a CuO/ZnO/Al2 O3 catalyst was prepared by a coprecipitation method, and mixed with ZSM-5 to form a bifunctional composite catalyst. The prepared catalyst is used in an alkylation reaction of benzene with synthesis gas in a liquid phase in a slurry bed reactor. A series of analytical methods such as ammonia gas temperature programmed desorption (NH3 -TPD), X-ray diffraction (XRD), nitrogen adsorption–desorption, scanning electron microscopy (SEM) and inductively coupled plasma emission spectrometry (ICP) were conducted to characterize the catalyst. The results show that the structure and acidity of the modified ZSM-5 have changed during the modification process, and ZSM-5 produces a more mesoporous structure after desiliconization. Therefore, the specific surface area of the modified ZSM-5 zeolite increases and the number of acid sites become smaller than those of the unmodified zeolite. The results show that the acid-modified ZSM-5 improves the conversion of CO, while the selectivity of CO to aromatics decreases. In contrast, only alkali modification and acid–alkali co-modification on ZSM-5 contributed to increasing the selectivity to aromatics, especially acid–alkali co-modified ZSM-5. The reason for this can be attributed to the fact that the modified zeolite produces a mesoporous structure, enhancing the mass transfer ability further. Moreover, the amount of strong acid sites on the modified ZSM-5 is reduced, which reduces the side reaction of methanol and olefin, thereby improving the selectivity of CO to aromatics.